2009
DOI: 10.1007/s10608-009-9257-7
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment and Depressotypic Cognitive Organization

Abstract: Recent research suggests that how information is organized in the mind may be important for determining one's vulnerability to depression. The purpose of the current study was to examine potential developmental precursors to a depressotypic cognitive organization (i.e., tightly-connected negative schemas and loosely-connected positive schemas) in a sample of young adult men and women (N = 91). The relation between childhood maltreatment (i.e., mother emotional maltreatment, father emotional maltreatment, physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…The results of this study indicate that emotional maltreatment influences emotional disorders directly and through some schemas as mediators which support past research by many authors (SHAFFER et al 2009;SHENK et al 2010;GIBB & ABELA 2008;LUMLEY & HARKNESS 2009;ABDOLAHZADEH RAFI 2014;LESSON & NIXON 2011) 1 . The mediation analysis suggested that early maladaptive schemas such as Anxiety.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study indicate that emotional maltreatment influences emotional disorders directly and through some schemas as mediators which support past research by many authors (SHAFFER et al 2009;SHENK et al 2010;GIBB & ABELA 2008;LUMLEY & HARKNESS 2009;ABDOLAHZADEH RAFI 2014;LESSON & NIXON 2011) 1 . The mediation analysis suggested that early maladaptive schemas such as Anxiety.…”
Section: Discussionsupporting
confidence: 90%
“…Tightly-interconnected negative schema organization predicts both anxiety and depression and loosely-interconnected positive schema organization demonstrates specificity to depression (Dozois 2007;Dozois andDobson 2001a, b, 2003;Dozois and Frewen 2006;Lumley and Harkness 2009;Segal et al 1995Segal et al , 1988. Longitudinal investigations of schema organization in depression demonstrate that cognitive organization is stable between depressive episodes, supporting the theory that these structures are enduring (Dozois and Dobson 2001a;Dozois 2007;Seeds and Dozois 2010).…”
Section: Cognitive Organization and Youth Depression Symptomsmentioning
confidence: 88%
“…Much less examined are potential developmental origins of depressotypic cognitive organization. In one exception, Lumley and Harkness (2009) demonstrated that cognitive organization was linked to experiences of childhood emotional and physical abuse in young adults. Parenting research suggests that even comparatively more subtle and widely experienced forms of negative parenting are implicated in models of risk.…”
Section: Perceptions Of Parenting and Cognitive Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, more attention has been directed toward understanding the common mechanisms and processes that may mediate risk transmission across development. For example, cognitive vulnerabilities such as cognitive schemas (e.g., Lumley & Harkness, 2009;Wright, Crawford, & Del Castillo, 2009), automatic negative self-associations (e.g., van Harmelen et al, 2010), and rumination (e.g., Raes & Hermans, 2008) have been proposed to arise from abuse experiences and potentially mediate the relationship between abuse and depression over time.…”
Section: Abuse Affect Regulation and Depressionmentioning
confidence: 99%